The first records of P. d. dexamenus from Costa Rica and new records of Prepona pylene gnorima (Nymphalidae: Charaxinae) - Murillo-Hiller, Luis Ricardo; Montero-Ramírez, José Joaquín (Zootaxa, 2010)
The genus Prepona Boisduval contains seven species (Lamas 2004), four of which occur in Costa Rica. Only one of these four species is common while the others can be very scarce and may not be seen for years. Due to their scarcity these species are very poorly known and there are few collection data, most of which are old records. The data in existence about distribution, behavior, and natural history are compiled not as major objectives, but instead are extra data obtained from other research. At this time the only information source for this genus in Costa Rica is DeVries (1987).